KRISIS REKOGNISI KEBUDAYAAN IDENTITAS ETNIS TIONGHOA DALAM PELESTARIAN MAKAM KAPITAN OEY KIAT TJIN DI KOTA TANGERANG - Rival Mubarok; Dinda Septiana Putri; Nicholas Matthew; M. Nabil Ijlal; Mahpudin (Program Studi Pemikiran Politik Islam, Fakultas Ushuluddin, Adab, dan Dakwah IAIN Palu, 2024)
The Kapitan Oey Kiat Tjin tomb site in Tangerang can be understood as an act of cultural relations in an area that captures social practices in the Kampung Baru housing complex. This site has become a topic of discussion which has an impact on the complexity of group interactions with the background of Chinese cultural heritage given the existence of the tomb. This is designed to classify cultural elements related to social dynamics which include customs, symbols and culture that play a role in building the identity of the Chinese community in the region, especially if we take Charles Taylor's theory of how identity is created by recognition, we can understand how the tomb of Oey Kiat Tjin is a socially constructive form built with heritage as well as cultural values that influence the perception of society in the Tangerang area. Taylor's recognition is not only based on formal formulations or from other institutions but instead emphasizes the values that direct the role and services of the captain. towards local development at that time which decorated the expression of self-identity and subject power by the Chinese community which had existed since the Dutch government to be appreciated and absorbed as a cultural habitus in regional aspects. The analytical results were presented in dialogue efforts and interviews with local sources.